Analisis Tindak Pidana Narkotika di Jakarta Selatan (Studi Kasus: Putusan Pengadilan Negeri Jakarta Selatan Nomor 391/Pid.Sus/2022/PN.JKT.SEL) - Rafli , Muhammad; Purba, Lilis (PT Elaborium Elevasi Indonesia, 2025)
This research activity aims to find out how the regulations related to narcotics crimes are in Indonesia and to find out whether the sanctions given by law enforcers in dealing with the occurrence of narcotics crimes in South Jakarta are appropriate. This type of research is descriptive empirical legal research with a qualitative approach. Data collection through observation and interviews. The analysis technique is qualitative, that is, the data obtained is arranged systematically and analyzed qualitatively. The results of this research indicate that the factors causing narcotics crimes in South Jakarta are caused by environmental factors, dependency factors, and family factors. Based on these factors, efforts were made by the Police and State Detention Center to reduce narcotics crimes, namely in the form of preventive efforts, repressive efforts and persuasive efforts.